Síntese e análise estrutural de compostos supramoleculares de Cd(II) com o ligante 4,6-dimetilpirimidina-2-tiona - Casagrande, Gleison Antonio (2004)
This dissertation describes the synthesis and analysis of the supramolecular compounds α- and β-[Cd(DMPYMT-S)2]n, DMPYMT-S = 4,6-dimethylpyrimidine-2- thione. The reaction product of cadmium acetate dihydrate with DMPYMT-S was dissolved in hot ethanol with a small quantity of DMSO or ammonium diethyldithiophosphate. Gradual evaporation of the solvent gave the crystallization products (1) or (2), respectively. Single crystal X-ray structural analysis for both products was carried out. Compound (1), solved and refined in the space group P21/c, shows a supramolecular structure formed by μ2-S–Cd secondary bonds parallel to the crystallographic a axis. Compound (2), solved and refined in the space group Pca21, possesses μ2-S–Cd and Npyrimidine–Cd secondary bonds to form a zig-zag supramolecular structure parallel to the crystallographic b axis. The Cd(II) atom in each structure is sp3 d2 hybridized with an octahedral geometry for (1) and a distorted octahedral geometry for (2). The structural control in the formation of the supramolecular compounds α- and β- [Cd(DYPYMT-S)2] is achieved by the use of complexing agents acting as coligands in the solubilization and crystallization processes. For the two compounds, the results of the C, H and N elemental analysis and infrared vibrational spectroscopy are included.